Development of rice water-saving and drought resistance quantitative evaluation system of wide water ecological range based on quantitative gradient water control - Kang, Haiqi; Hassan, Muhammad Ahmad; Kang, Jiarong; Luo, Yuehua; Zhang, Hong; Zeng, Yongxuan; Fu, Guanfu; Qin, Rongmin; Xu, Deze; Wang, Shimei (Frontiers in Plant Science, 2025)
The drought resistance of rice is an indirect observational and complex trait whose phenotype is reflected in the response of directly observational traits to drought stress. To objectively and accurately evaluate the drought resistance of rice, soil moisture gradient quantification was designed as a general water index among different soil types. Through soil water control, water consumption calculation, yield test, trait examination, and statistical analysis, the relationship between quantitative water control treatment and rice yield drought resistance was studied to establish a quantitative and controllable evaluation system of rice drought resistance. Four kinds of gradients, namely, 100%, 80%, 60%, and 40% field moisture capacity, were designed in the experiment. Six tested rice varieties grew under the long-term water control treatment. Six varieties grew under four levels of field moisture capacity from transplanting and returning to green to maturity. The calculation of actual field moisture shows that the four design levels formed a significant gradient and reached a very significant difference. The gradient and quantitative water control (GQWC) significantly influenced tiller formation, grain yield, yield component traits, and water use efficiency. Under the designed GQWC treatment, the difference in yield drought resistance of tested rice varieties is reflected under wide water ecological amplitude. There was a significant difference between varieties and traits, and the relationship between traits and varieties was very significantly different under different GQWC levels. The differences in drought resistance among varieties differ due to various water gradients and direct observational traits. It is difficult to evaluate drought resistance accurately with a single gradient. Considering yield components and water use efficiency, it is the best choice for a comprehensive index with multi-gradient yield drought resistance. Based on the index mapping of gradient drought resistance and area calculations, 28 evaluation indices of drought resistance were calculated in parallel, and six indices with better evaluation effect were screened to solve the optimal comprehensive index, namely, the sum of drought resistance index under multi-gradient with multi-traits (MG_MT_DI_SUM), the sum of drought resistance index of yield under multi-gradient (MG_Y_DI_SUM), the product of total area under the curve of drought resistance index under multi-gradient with multi-traits (MG_MT_DI_TAUC_MUL), the drought resistance index of yield under the second gradient (SGII_Y_DI), the comprehensive value of membership function of the total area under the curve of drought resistance index with multi-gradient and multi-traits (MG_MT_DI_SUM), and the logarithm of total area under the curve of drought resistance index with multi-gradient and multi-traits (MG_MT_DI_TAUC_LOG). Among these indices, 100*MG_MT_DI_TAUC_LOG and 5*MG_Y_DI_SUM were the ideal evaluation indices, which could be used as the main indices for the comprehensive evaluation of rice drought resistance under the GQWC test.